The Critical Role of Tetrahydrobiopterin (BH4) Metabolism in Modulating Radiosensitivity: BH4/NOS Axis as an Angel or a Devil - Feng, Yang; Feng, Yahui; Gu, Liming; Liu, Pengfei; Cao, Jianping; Zhang, Shuyu (Frontiers in Oncology, 2021)
Ionizing radiation and radioactive materials have been widely used in industry, medicine, science and military. The efficacy of radiotherapy and adverse effects of normal tissues are closed related to cellular radiosensitivity. Molecular mechanisms underlying radiosensitivity are of significance to tumor cell radiosensitization as well as normal tissue radioprotection. 5,6,7,8-Tetrahydrobiopterin (BH4) is an essential cofactor for nitric oxide synthases (NOS) and aromatic amino acid hydroxylases, and its biosynthesis involves de novo biosynthesis and a pterin salvage pathway. In this review we overview the role of BH4 metabolism in modulating radiosensitivity. BH4 homeostasis determines the role of NOS, affecting the production of nitric oxide (NO) and oxygen free radicals. Under conditions of oxidative stress, such as UV-radiation and ionizing radiation, BH4 availability is diminished due to its oxidation, which subsequently leads to NOS uncoupling and generation of highly oxidative free radicals. On the other hand, BH4/NOS axis facilitates vascular normalization, a process by which antiangiogenic therapy corrects structural and functional flaws of tumor blood vessels, which enhances radiotherapy efficacy. Therefore, BH4/NOS axis may serve as an angel or a devil in regulating cellular radiosensitivity. Finally, we will address future perspectives, not only from the standpoint of perceived advances in treatment, but also from the potential mechanisms. These advances have demonstrated that it is possible to modulate cellular radiosensitivity through BH4 metabolism.